People with higher autistic traits show stronger binding for color-shape associations - Chen, N; Watanabe, K; Spence, C; Wada, M (Springer Nature, 2023)
Non-synesthetes exhibit a tendency to associate specific shapes with particular colors (i.e., circle-red, triangle-yellow, and square-blue). Such color-shape associations (CSAs) could potentially affect the feature binding of colors and shapes, thus resulting in people reporting more binding errors in the case of incongruent, rather than congruent, colored-shape pairs. Individuals with autism spectrum disorder (ASD) exhibit atypical sensory processing and impaired multisensory integration. Here, we examined whether autistic traits ﻿(Autism-Spectrum Quotient; AQ) influence the strength of color-shape associations, as evidenced by the occurrence of binding errors in incongruent minus congruent conditions. Participants took part in an experiment designed to reveal binding errors induced by incongruent and congruent colored-shape pairs, and completed the Japanese version of the AQ score. The results revealed a significant correlation between AQ scores and occurrence of binding errors when participants were presented with the circle-red and triangle-yellow CSAs: That is, individuals with higher autistic traits tend to make more binding errors in incongruent minus congruent colored-shape pairs, indicating a stronger binding of circle-red and triangle-yellow associations. These results therefore suggest that autistic traits play a role in forming color-shape associations, shedding light on the nature of both color-shape associations and autistic perception.